Upaya Pemberian Edukasi Pencegahan Penyakit Jantung Berbasis Budaya Gandrung Banyuwangi: The Efforts to Provide Education on Heart Disease Prevention Based on Gandrung Banyuwangi Culture - Prasetyo, Joko; Gustian, Citra Indra; Suhita, Byba Melda (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Community knowledge plays a crucial role in preventing heart disease. This community service activity, conducted by doctoral students of the Public Health Program at Universitas Strada Indonesia in collaboration with the Dewan Kesenian Blambangan of Banyuwangi Regency, aimed to enhance knowledge regarding heart disease prevention among Gandrung artists in Banyuwangi. The activity was delivered through a workshop utilizing lectures and interactive discussions. A total of 30 participants, consisting of Gandrung dancers, musicians, and make-up artists, took part in the program. Participants' knowledge was assessed using pre-test and post-test evaluations. The results demonstrated a significant improvement, with the proportion of participants possessing good knowledge increasing from 6.67% to 83.33% after the workshop. These findings confirm that a culturally based Gandrung education program is efficacious in improving participants' knowledge. The integration of health education with local wisdom successfully created a model that is both relevant and well-received by the community. This activity highlights that health education through the Gandrung cultural approach serves as an effective and innovative strategy to enhance public knowledge and understanding of heart disease prevention.